The development of land management in Yakutia in Soviet times - Arkhipov I. V. (Relevant lines of scientific research: theory and practice, 2017)
land management in Yakutia developed at different times in different ways and had its own historical stages. The paper considers the development of land management in our republic during the Soviet period after the Great Patriotic War, as well as during the «stagnation» period. The work of land surveyors of Yakutia at that time is shown, the available materials of various authors and their memories are used. The ppurpose of this work is to study the role of land surveyors in Yakutia in socio-economic development of the country and their personal deposit in the development of Yakutia, one of the largest regions in our country.
Keywords: землеустройство; land management; землеустроители; Управление землеустройства и севооборотов; земэкспедиция; Росгипрозем; Дальгипроозем; государственный учет земель; инвентаризация земель; land surveyors; land management and crop rotation department; land forwarding agency; Rosgiprozem; Dalgiproozem; state land registration; land inventory